ANALISA KETINGGIAN PERMUKAAN AIR LAUT BERBASIS TEKANAN ATMOSFER UNTUK SISTEM PERINGATAN DINI TSUNAMI - Ledy Manuhutu; Yono Hadi Pramono (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Have analyzed sea-level atmospheric pressure using a barometer-based altitude. From the measurement results obtained that any change in the height of one meter will change the pressure 0f 0,166 millibars. It can then be applied in the tools tsunami early warning system that has been in design (